2023
DOI: 10.3389/fpls.2023.1183249
|View full text |Cite
|
Sign up to set email alerts
|

Cadmium exposure is associated with increased transcript abundance of multiple heavy metal associated transporter genes in roots of hemp (Cannabis sativa L.)

Amanda O. Marabesi,
Savithri U. Nambeesan,
Marc W. van Iersel
et al.

Abstract: Industrial hemp (Cannabis sativa L.) has demonstrated promise for phytoremediation due to an extensive root system, large biomass, and ability to survive under relatively high levels of heavy metals. However, little research has been conducted to determine the impact of heavy metal uptake in hemp grown for medicinal use. This study evaluated the potential for cadmium (Cd) uptake and its impact on growth, physiological responses, and transcript expression of metal transporter genes in a hemp variety grown for f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 56 publications
2
3
0
Order By: Relevance
“…In contrast, the DLS variety, T1 had similar Cd concentrations in roots, leaf, and stem tissue upon exposure to Cd. These results are consistent with previous literature, which reported that roots were the preferred tissue for Cd accumulation in hemp [27,34,35,40,41] and that Cd accumulation increased with increasing Cd concentrations in the growing media [39]. For instance, Cd concentrations in the roots of C. sativa fiber variety Santhica 27 exposed to 20 µM Cd (2.25 mg•L −1 Cd) for one week averaged 2687 mg•kg −1 dw, while Cd concentrations in stems and leaves averaged 1243 mg•kg −1 dw and 717 mg•kg −1 dw, respectively [34].…”
Section: Concentration In Hemp Tissuessupporting
confidence: 93%
See 4 more Smart Citations
“…In contrast, the DLS variety, T1 had similar Cd concentrations in roots, leaf, and stem tissue upon exposure to Cd. These results are consistent with previous literature, which reported that roots were the preferred tissue for Cd accumulation in hemp [27,34,35,40,41] and that Cd accumulation increased with increasing Cd concentrations in the growing media [39]. For instance, Cd concentrations in the roots of C. sativa fiber variety Santhica 27 exposed to 20 µM Cd (2.25 mg•L −1 Cd) for one week averaged 2687 mg•kg −1 dw, while Cd concentrations in stems and leaves averaged 1243 mg•kg −1 dw and 717 mg•kg −1 dw, respectively [34].…”
Section: Concentration In Hemp Tissuessupporting
confidence: 93%
“…This suggests that the DLS varieties used in the present study may be more tolerant to Cd exposure at 2.5 mg•L −1 than the DN varieties evaluated. These results agree with previous studies that have reported a decrease in shoot biomass of hemp plants exposed to Cd [26,34,35,39].…”
Section: Plant Height and Biomass Yieldsupporting
confidence: 93%
See 3 more Smart Citations